Generalised resilience models for power systems and dependent infrastructure during extreme events. Issue 2 (18th March 2020) - Krishnamurthy, Vaidyanathan; Huang, Bing; Kwasinski, Alexis; Pierce, Evan; Baldick, Ross
Abstract : This study presents a generalised critical infrastructures resilience model for extreme events with a focus on power grids. Infrastructures are modelled as three domains – physical, cyber, and human. Each domain is described with respect to the services it provides. Each domain is represented by geometric graphs for each service it provides. The resilience models use geometric graphs with each graph's nodes and edges characterised based on relevant attributes. This study also discusses various applied aspects related to resilience models including the impact of changing operating environment, human‐driven processes, such as logistics, and service buffers. Due to their stated particular importance in the U.S. Presidential Policy Directive 21, particular attention is placed on the power infrastructure and its impact on the public communication infrastructures as a main critical load. This study focuses on the multi‐time scale power system operation to capture cascading outages within, and subsequently to its dependent infrastructure – the public communication system (e.g. wireless or 'cellular' communication networks) as a main critical load. This study illustrates the merits of the proposed models in calculating resilience in extreme events and derives physical domain representation for electric and communication systems using cell tower and substation data from the USA.